2022
DOI: 10.1007/s00418-021-02065-x
|View full text |Cite
|
Sign up to set email alerts
|

The role of oviduct-specific glycoprotein (OVGP1) in modulating biological functions of gametes and embryos

Abstract: Diverse lines of evidence indicate that the mammalian oviduct makes important contributions to the complex process of reproduction other than being simply a conduit for the transport of gametes and embryos. The cumulative synthesis and transport of proteins secreted by oviductal secretory cells into the oviductal lumen create a microenvironment supporting important reproductive events, including sperm capacitation, fertilization, and early embryo development. Among the components that have been identified in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 112 publications
1
14
0
Order By: Relevance
“…OVGP1 is a secretory glycoprotein that was reported to be highly expressed in ovarian tissues. 22 Our results showed that OVGP1 was broadly expressed in mouse tissues, including heart, liver, kidney, spleen, lung, brain, oviduct, and arterial tissues (Figure S3), indicating that OVGP1 derived from other tissues may participate in the regulation of BP. The expression of OVGP1 was not associated with the sex of either humans or mice (Figure S4).…”
Section: Resultsmentioning
confidence: 73%
See 1 more Smart Citation
“…OVGP1 is a secretory glycoprotein that was reported to be highly expressed in ovarian tissues. 22 Our results showed that OVGP1 was broadly expressed in mouse tissues, including heart, liver, kidney, spleen, lung, brain, oviduct, and arterial tissues (Figure S3), indicating that OVGP1 derived from other tissues may participate in the regulation of BP. The expression of OVGP1 was not associated with the sex of either humans or mice (Figure S4).…”
Section: Resultsmentioning
confidence: 73%
“…OVGP1 (oviduct glycoprotein 1) is an estrogen-induced secretory protein in the oviduct that aids in sperm capacitation, fertilization, and early embryonic development. 22 Whether OVGP1 participates in hypertension remains unclear. A genome-wide scan performed in the Québec Family Study revealed that the chromosome 1p22.3-1p13.1 region was associated with an increase in arterial systolic BP.…”
mentioning
confidence: 99%
“…Among oviductal factors identified in the oviductal fluid, OVGP1 has been well characterized and suggested to play important roles in the process of several mammalian species, including humans [for review, see Araki & Yoshida-Komiya, 1998; Buhi 2002; Avilés et al, 2010; González-Brusi et al, 2020; Zhao et al, 2022]. Using the golden hamster as a model, which has provided a wealth of knowledge concerning the mammalian reproductive process [Hirose & Ogura, 2019], Ovgp1 -knockout (KO) animals were generated using gene editing technology (Suppl.…”
Section: Resultsmentioning
confidence: 99%
“…Among oviductal factors identified in the oviductal fluid, OVGP1 has been well characterized and suggested to play important roles in the process of several mammalian species, including humans [for review, see Araki & Yoshida-Komiya, 1998;Buhi 2002;Avilés et al, 2010;González-Brusi et al, 2020;Zhao et al, 2022].…”
Section: Generation Of Ovgp1-deficient Hamstersmentioning
confidence: 99%
“…Apart from ovarian follicular development, oviductal fluid in the lumen of the oviduct provides an important milieu for gamete maturation and fertilization. Zhao et al (2022) reviewed the identification and characterization of oviduct-specific glycoprotein (OVGP1) and its functions in various mammalian species, including humans. OVGP1 plays a key role in sperm capacitation, fertilization, and early embryo development.…”
Section: Female Partmentioning
confidence: 99%